1995
DOI: 10.1089/dna.1995.14.931
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Silencer, Enhancer, and Basal Promoter Region in the Human CD95 (Fas/APO-1) Gene

Abstract: Genomic clones for the human CD95 (Fas/APO-1) and CD40 genes have been isolated and 2.3 kb of the CD95 and 0.8 kb of the CD40 gene 5'-flanking regions sequenced. Comparisons of the human CD95 gene with the human CD40 and the murine CD40 and TNFR-II genes showed a low degree of sequence similarity. However, dot matrix analyses revealed conservation of two stretches between human CD95 (-387 to -362 and -288 to 261 in CD95) and murine TNFR-II genes. Additionally, TCCTCC motifs are present within 400 bp up-stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…The increased expression of Fas/Apo-1 as the only peculiar finding shared by mother and son might be a candidate. Alternatively, as multiple transcriptional start sites have been found in the fas/apo-1 promoter region, gene regulation may account to the pathogenesis of ALPS/ CSS (Rudert et al, 1995). It seems reasonable that episodes of pancytopenia during infection as observed in our patient result from stimulation of fas/apo-1 transcription as demonstrated for influenza infection by Wada and coworkers (Wada et al, 1995).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The increased expression of Fas/Apo-1 as the only peculiar finding shared by mother and son might be a candidate. Alternatively, as multiple transcriptional start sites have been found in the fas/apo-1 promoter region, gene regulation may account to the pathogenesis of ALPS/ CSS (Rudert et al, 1995). It seems reasonable that episodes of pancytopenia during infection as observed in our patient result from stimulation of fas/apo-1 transcription as demonstrated for influenza infection by Wada and coworkers (Wada et al, 1995).…”
Section: Discussionsupporting
confidence: 53%
“…Patient RT and his father were shown to carry a point mutation at position 804 resulting in an A 804 C exchange when compared with the published sequences (Behrmann et al, 1994;Rudert et al, 1995). This mutation causes a single amino acid exchange at position 268 of the Fas/Apo-1 molecule (Q 268 P).…”
Section: Analyses Of Transcripts and Protein Expressionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that plenty of CpG motifs exist in the promoter region of apoptosis-inducing TNF receptor superfamily genes (29) and that apoptotic signaling pathways are often subjected to epigenetic gene silencing (19,30). However, with the exception of the study by Petak et al (31), who showed an inverse correlation between the methylation status of the Fas gene promoter and Fas protein expression by comparing different tumor cell lines, the promoter activity of apoptosis-inducing genes was not directly studied in the same cell.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis using reporter constructs and transient transfections identified a silencer activity residing in the promoter of the Fas gene. 38 Yin Yang-1 (YY1) is a DNAbinding zinc-finger transcription factor functioning as an activator, a repressor, and an initiator of transcription. 39 Nitric oxide (NO) has been implicated in transcriptional control, and serves as an intracellular second messenger to modify gene expression.…”
Section: Discussionmentioning
confidence: 99%